Kala-azar in Qadisiah : A clinicoepidemiological descriptive study - Al-Shamsi, Mohammed mojar; mohsin, Rahman Kareem; Abdullah, Assad Habeeb (Journal of the Faculty of Medicine Baghdad, 2008)
Subject and Method : study involved sixty five children with kala-azar who were admitted to the maternity and children teaching hospital in Diwaniah during a one year period , 1999. The clinical and epidemiological criteria of the disease were discussed. The majority of these patients were under the age of 5 years ( 97% ) and were from rural areas ( 86% ) Result : The symptoms and signs of the disease were fever (100% ), splenomegaly (100% ), anaemia ( 100% ), hepatomegaly ( 92% ), anorexia ( 62% ), bleeding tendency ( 46% ) and jaundice ( 31% ). Our patients had high incidence of bleeding tendency , jaundice , edema and relatively high mortality in comparison with patients elsewhere